2021
DOI: 10.3390/oral1010004
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Silicate Cements vs. Epoxy Resin Based Cements: Narrative Review

Abstract: In recent years, calcium silicate cements have been introduced. The purpose of this study is to analyze the main differences between calcium silicate-based cements and epoxy resin-based cements, analyzing the scientific literature of the last year to highlight the main advantages for predictable clinical use. Data collected from the included studies were used in order to analyze different features: chemical-physical properties, cytotoxicity and cell migration, inflammatory response, mineralizing and osteogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The homogeneity of root canal obturation highly depends on the porosity of the fillings [ 25 ], as open pores communicating with dentinal walls may create an excellent pathway for microleakage and eventually decrease the success rate and outcome of endodontic treatment [ 28 , 36 ]. Closed pores are considered to be less clinically relevant, as they represent empty spaces completely surrounded by filling material [ 37 ]. Nevertheless, it has been shown that this type of porosity may negatively affect the physical properties of the material, such as hardness and strength [ 36 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The homogeneity of root canal obturation highly depends on the porosity of the fillings [ 25 ], as open pores communicating with dentinal walls may create an excellent pathway for microleakage and eventually decrease the success rate and outcome of endodontic treatment [ 28 , 36 ]. Closed pores are considered to be less clinically relevant, as they represent empty spaces completely surrounded by filling material [ 37 ]. Nevertheless, it has been shown that this type of porosity may negatively affect the physical properties of the material, such as hardness and strength [ 36 , 38 ].…”
Section: Discussionmentioning
confidence: 99%